Effect of Yucca schidigera and Natural Zeolite on Broiler Performance - Cabuk, M.; Alcicek, A.; Bozkurt, M.; Akkan, S. (International Journal of Poultry Science, 2004)
The effects of dietary supplementation of Yucca schidigera and natural zeolite on broiler performance, ammonia concentration of broiler house, litter moisture, fecal dry matter and fecal crude ash were investigated. One day-old, nine hundred and sixty unsexed broiler chicks obtained from a commercial hatchery were divided into 4 treatment groups of 240 birds each. Birds were randomly assigned to the four treatment diets, consist of control, 15 g natural zeolite/kg, 25 g natural zeolite/kg and 120 mg Yucca schidigera/kg. Body weights of birds were significantly (P